2014
DOI: 10.1038/ejhg.2014.230
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete penetrance and phenotypic variability of 6q16 deletions including SIM1

Abstract: 4,5,6 6q16 deletions have been described in patients with a Prader-Willi-like (PWS-like) phenotype. Recent studies have shown that certain rare single-minded 1 (SIM1) loss-of-function variants were associated with a high intra-familial risk for obesity with or without features of PWS-like syndrome. Although SIM1 seems to have a key role in the phenotype of patients carrying 6q16 deletions, some data support a contribution of other genes, such as GRIK2, to explain associated behavioural problems. We describe 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 51 publications
3
16
0
2
Order By: Relevance
“…Macrocephaly and tall stature and/or obesity are shared physical findings in some patients compatible with a contribution of the genomic region to growth regulation. El Khattabi et al suggested an involvement of the MCHR2 and SIM1 genes in behavioural disorders and SIM1 in obesity [19]. Both genes are not located within the deleted region of our patient.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Macrocephaly and tall stature and/or obesity are shared physical findings in some patients compatible with a contribution of the genomic region to growth regulation. El Khattabi et al suggested an involvement of the MCHR2 and SIM1 genes in behavioural disorders and SIM1 in obesity [19]. Both genes are not located within the deleted region of our patient.…”
Section: Discussionmentioning
confidence: 52%
“…[19] and Le Caignec et al [20] reported on patients with mostly larger heterozygous deletions in 6q16 (in a range between 1.7 and 14 Mb) which do not allow specific phenotype-genotype correlations. However, their patients, the patients summarized in Table 1 and our patient share phenotypic findings such as hypotonia, intellectual disability, developmental delay as well as autistic features or behavioural anomalies reminiscent of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Although a variety of deletions have been reported to cause Prader-Willi related phenotypes, the most common PWL deletion is the 6q16 deletion comprising the bHLH-PAS family transcription factor SIM1 [20-22]. Sim1 heterozygous mice display hyperphagic obesity and reduced oxytocin expression in the hypothalamus [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…However, some mutations of SIM1 have incomplete penetrance and variable phenotype [57]. The similar phenotype between patients with SMI1 and MC4-R deficiency suggests that some effects of SIM1 are mediated by altered melanocortin signaling.…”
Section: Sim1 Deficiencymentioning
confidence: 99%